Faith and the founders of the American republic - Dreisbach, Daniel L.; Hall, Mark David, 1966- (New York : Oxford University Press, 2014)
The role of religion in the founding of America has long been a hotly debated question. Some historians have regarded the views of a few famous founders, such as Benjamin Franklin, Thomas Jefferson, James Madison, and Thomas Paine, as evidence that the founders were deists who advocated the strict separation of church and state. Popular Christian polemicists, on the other hand, have attempted to show that virtually all of the founders were pious Christians in favor of public support for religion. As the essays in this volume demonstrate, a diverse array of religious traditions informed the political culture of the American founding. Faith and the Founders of the American Republic includes studies both of minority faiths, such as Islam and Judaism, and of major traditions like Calvinism. It also includes nuanced analysis of specific founders -- Quaker fellow-traveler John Dickinson, prominent Baptists Isaac Backus and John Leland, and theistic rationalist Gouverneur Morris, among others -- with attention to their personal histories, faiths, constitutional philosophies, and views on the relationship between religion and the state. This volume will be a crucial resource for anyone interested in the place of faith in the founding of the American constitutional republic, from political, religious, historical, and legal perspectives.
Deism and the founders / Darren Staloff -- Vindiciae, contra tyrannos : the influence of the Reformed tradition in the American founding / Mark David Hall -- Jews, Judaism and the American founding / David G. Dalin -- The founders and Islam / Thomas S. Kidd -- Religion and the Loyalists / Robert M. Calhoon, Ruma Chopra -- The antifederalists and religion / Donald L. Drakeman -- The Bible and the political culture of the American founding / Daniel L. Dreisbach -- Religion, race, and the founders / Jonathan D. Sassi -- Gouverneur Morris and theistic rationalism in the founding era / Gregg Frazer -- John Hancock: Congregationalist revolutionary / Gary Scott Smith -- Elias Boudenot, Presbyterians, and the quest for a "righteous republic" / Jonathan Den Hartog -- The Quaker contributions of John Dickinson to the creation of the American republic / Jane E. Calvert -- Isaac Backus and John Leland : Baptist contributions to religious liberty in the founding era / Joe L. Coker
Includes index.
Includes bibliographical references and index.
Keywords: Religion and politics -- United States -- History -- 18th century; United States -- Religion -- To 1800.; Religion and state -- United States -- History -- 18th century; Founding Fathers of the United States -- Religious life